2019
DOI: 10.1186/s12893-019-0602-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy analysis of two surgical treatments for thoracic and lumbar intraspinal tumours

Abstract: Background Surgery remains the main curative option for the treatment of intraspinal tumour. The purpose of the present study was to analyze the clinical outcomes of laminoplasty with process-lamina complex replantation compared with laminectomy with pedicle screw fixation for intraspinal tumours. Methods In our retrospective analysis, 27 patients received tumour resection surgery by laminoplasty with reconstruction plate fixation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…17 Our design is based on a clinical surgical procedure called lamina replantation which replanted the lamina and spinal ligaments to stabilize the spine, prevent hypertrophic epidural fibrosis and have been reported achieving good clinical outcomes. [18][19][20] In the possible clinical setting, the surgical procedures of our design can be performed like lamina replantation. Briefly, after usual decompression with retaining the supraspinous and interspinous ligaments, the artificial lamina will be fixed by pedicle screws and the supraspinous and interspinous will be reconstructed by thick silk threads through the pilot hole designed pre-operation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our design is based on a clinical surgical procedure called lamina replantation which replanted the lamina and spinal ligaments to stabilize the spine, prevent hypertrophic epidural fibrosis and have been reported achieving good clinical outcomes. [18][19][20] In the possible clinical setting, the surgical procedures of our design can be performed like lamina replantation. Briefly, after usual decompression with retaining the supraspinous and interspinous ligaments, the artificial lamina will be fixed by pedicle screws and the supraspinous and interspinous will be reconstructed by thick silk threads through the pilot hole designed pre-operation.…”
Section: Discussionmentioning
confidence: 99%
“…Zong et al [ 4 ] have reported that the total laminectomy and screw-rod internal fixation significantly reduced the incidence of spinal structural instability and kyphosis to some extent, comparing with the classical total laminectomy, in short-term follow-up. However, due to the loss of posterior bone structure, the scar tissue is still the risk of spinal cord compression after operation [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laminoplasty has the obvious advantage of reducing the postoperative risks of classical total laminectomy by rebuilding the integrity of the posterior elements. Following the first report of lamina replantation by Raimondi in 1976 [ 7 ], a variety of laminoplasty, with a good satisfactory surgical results, has been used to treat patients with intraspinal tumors [ 5 , 6 , 8 10 ]. In addition, because the laminoplasty retains the relatively normal posterior structure, it can help avoid the epidural scar adhesion and contraction of the dura mater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, more and more surgeons are aware of the importance of reconstruction of spinal stability and reducing postoperative complications for postoperative recovery and quality of life of patients, and pay great attention to the maintenance of spinal stability during operation. Following the introduction of lamina replantation by Raimondi in 1976 5 , a series of laminoplasty has been developed for intraspinal tumor resection [6][7][8][9][10] . By preserving some or all of the posterior column elements, these techniques restore the stability and integrity of the posterior column structure of spine and significantly reduce the complications of classical total laminectomy.…”
Section: Introductionmentioning
confidence: 99%